Cardiac death after breast radiotherapy and the QUANTEC cardiac guidelines. (November 2019) - Beaton, Laura; Bergman, Alanah; Nichol, Alan; Aparicio, Maria; Wong, Graham; Gondara, Lovedeep; Speers, Caroline; Weir, Lorna; Davis, Margot; Tyldesley, Scott
Highlights: Cardiovascular risk factors predict for cardiac death after breast radiotherapy. Cardiovascular risk factors should be modified in breast cancer patients. Radiation induced cardiac death at 10-years is low if mean heart dose is <3.3 Gy. Radiation induced cardiac death at 10-years is low if maximum LAD dose is <45.4 Gy. Studies are needed to evaluate heart and LAD constraints in the CT-planning era. Abstract: Background: Breast/chest wall irradiation (RT) increases risk of cardiovascular death. International Quantitative Analysis of Normal Tissue Effects in the Clinic (QUANTEC) guidelines state for partial heart irradiation a "V25Gy <10% will be associated with a <1% probability of cardiac mortality" in long-term follow-up after RT. We assessed whether women treated with breast/chest wall RT 10-years ago who died of cardiovascular disease (CVD) violated QUANTEC guidelines. Materials/methods: A population-based database identified all cardiovascular deaths in women with early-stage breast cancer <80 years, treated with adjuvant breast/chest wall RT from 2002 to 2006. Ten-year rate of cardiovascular death was calculated using a Kaplan-Meier method. Patients were matched on a 2:1 basis with controls that did not die of CVD. For left-sided cases, the heart and left anterior descending (LAD) artery were retrospectively delineated. Dose-volume histograms were calculated, and heart V25Gy compared to QUANTEC guidelines. Results: 5249 eligible patients received breast/chest wall RT from 2002 to 2006: 76 (1.4% at 10-years) died of CVD by June 2015. Forty-two patients received left-sided RT (1.7% CVD death at 10-years), 34 right-sided RT (1.3% at 10-years). Heart V25Gy did not exceed 10% in any left-sided cases. No cardiac dosimetry parameter distinguished left-sided cases from controls. Conclusions: QUANTEC guidelines were not violated in any patient that died of CVD after left-sided RT. The risk of radiation induced cardiac death at 10-years appears to be very low if MHD is <3.3 Gy and maximum LAD dose (EQD23 Gy) is <45.4 Gy. Further studies are needed to evaluate heart and LAD constraints in the CT-planning era.